1999
DOI: 10.1074/jbc.274.25.18087
|View full text |Cite
|
Sign up to set email alerts
|

A Vanadium and Iron Cluster Accumulates on VnfX during Iron-Vanadium-cofactor Synthesis for the Vanadium Nitrogenase inAzotobacter vinelandii

Abstract: The vnf-encoded nitrogenase from Azotobacter vinelandii contains an iron-vanadium cofactor (FeV-co) in its active site. Little is known about the synthesis pathway of FeV-co, other than that some of the gene products required are also involved in the synthesis of the ironmolybdenum cofactor (FeMo-co) of the widely studied molybdenum-dinitrogenase. We have found that VnfX, the gene product of one of the genes contained in the vnf-regulon, accumulates iron and vanadium in a novel V-Fe cluster during synthesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
25
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…It has been described previously that in A. vinelandii CA11.1 most of the 49 V accumulates on VnfX, as seen in Fig. 1, lane 1, in the form of a vanadium-containing Fe-S cluster (16).…”
Section: Transfer Of 49 V From Vnfx To Nif-apodinitrogenase 4523mentioning
confidence: 88%
See 4 more Smart Citations
“…It has been described previously that in A. vinelandii CA11.1 most of the 49 V accumulates on VnfX, as seen in Fig. 1, lane 1, in the form of a vanadium-containing Fe-S cluster (16).…”
Section: Transfer Of 49 V From Vnfx To Nif-apodinitrogenase 4523mentioning
confidence: 88%
“…It has been reported that the V-Fe-S cluster accumulating on VnfX in extracts of A. vinelandii CA11.1 contains no or very low levels of homocitrate (16). To test whether homocitrate incorporation into the unfinished cluster occurs in vitro, we studied the effect of homocitrate analogues on the reaction.…”
Section: Transfer Of 49 V From Vnfx To Nif-apodinitrogenase 4523mentioning
confidence: 99%
See 3 more Smart Citations